Social Innovation - Zu, Liangrong (Encyclopedia of Corporate Social Responsibility, 2013)
Keywords: Ouvrages de référence; Réservé UdeM

Corporate Social Innovation - Gupta, Ananda Das (Encyclopedia of Corporate Social Responsibility, 2013)
Corporate social innovation is also called sustainable innovation. Corporate social innovation is about creating a good business by having sustainability as a focal point when the corporation develops a new product or service. This entails developing products or services which may relieve some of the world’s problems, such as disease, contaminated water, CO2 emission, hunger, or the lack of education. CSI is also referred to as CSR innovation. CSI is useful for businesses which work with innovation and/or CSR (corporate social responsibility).
Keywords: Ouvrages de référence; Responsabilité sociétale des entreprises; Réservé UdeM